Building Democratic Elections: A Critical Analysis of Efforts to Improve the Quality of Democracy - Nur , Febriansyah; Burhanuddin; Wahyu (Constitutional Law Review, 2025)
General elections are the main instrument of democracy as a manifestation of people's sovereignty and the legitimacy of power. However, the practice of democracy in Indonesia still faces serious challenges such as money politics, low voter participation, socio-political polarization, and weak integrity of election organizers. This study uses a normative approach with descriptive qualitative analysis to examine the effectiveness of elections in realizing substantial democracy according to constitutional principles. The results of the analysis show that these problems are not only technical, but also structural and cultural, reflecting the inequality between procedural and substantive democracy. Elections have not been fully able to become a political mechanism that produces representative and socially just government. This study also enriches the discourse on constitutional democracy by emphasizing the importance of recontextualizing the principle of rule of law in the electoral system. Meanwhile, in terms of policy, this study recommends strengthening regulations on the practice of money politics, increasing the institutional capacity of election organizers, and mainstreaming political education as a long-term strategy to build citizens' democratic awareness. By improving the legal design and practice of electoral politics, elections can function not only as a five-year political ritual, but also as a means of social transformation towards a more substantial, inclusive, and sustainable democracy